Culture an empirical investigation of beliefs, work, and fertility - Fernández, Raquel 1959-; Fogli, Alessandra (National Bureau of Economic Research, 2005)
"We study the effect of culture on important economic outcomes by using the 1970 Census to examine the work and fertility behavior of women 30-40 years old, born in the U.S., but whose parents were born elsewhere. We use past female labor force participation and total fertility rates from the country of ancestry as our cultural proxies. These variables should capture, in addition to past economic and institutional conditions, the beliefs commonly held about the role of women in society, i.e. culture. Given the different time and place, only the beliefs embodied in the cultural proxies should be potentially relevant to women's behavior in the US in 1970. We show that these cultural proxies have positive and significant explanatory power for individual work and fertility outcomes, even after controlling for possible indirect effects of culture (e.g., education and spousal characteristics). We examine alternative hypotheses for these positive correlations and show that neither unobserved human capital nor networks are likely to be responsible. We also show that the effect of these cultural proxies is amplified the greater is the tendency for ethnic groups to cluster in the same neighborhoods"--National Bureau of Economic Research web site.
Keywords: Frau; Gesellschaft; Wirtschaft; Birth control -- Social aspects; Children of immigrants -- Employment -- United States; Children of immigrants -- United States -- Economic conditions; Children of immigrants -- United States -- Population; Fertility, Human -- Social aspects; Women -- Employment -- Social aspects; Women -- Employment -- United States; Women -- United States -- Economic conditions; USA